A voyage towards the South Pole, and round the world : performed in His Majesty's ships the Resolution and Adventure, in the years 1772, 1773, 1774, and 1775 - Cook, James, 1728-1779 (Printed for W. Strahan ;, 1777)
Volume 1 of a 2 volume set. For individual volumes in the set see CIHM nos. 67489-67490.